The role of Islam in foreign policymaking - Hadžikadunić, Emir (Context: Journal of Interdisciplinary Studies, 2022)
Religion has often been an ignored dimension of statecraft, particularly so by realist or neorealist schools. This article explores the question of how a number of states, in which all or a considerable part of the population is Muslim, incorporate Islam as a guiding principle into their broader foreign policy. In this regard, it reviews a selected number of foreign policy cases using individual, domestic and international levels of analysis in which diverse Islamic incentives from major theoretical perspectives interplay with foreign policy. Its ultimate objective is to provide a deeper synthesis of the literature on Islam in foreign policymaking and relating it to major IR theories.